Extremophilic Microorganisms: An Alternative as Synthesizers of Ferromagnetic Nanoparticles. - Blamey-Alegria, J (IEEE, 2024)
The development of new alternatives for the synthesis of nanoparticles (NPs) has been of great interest. Chemical synthesis has traditionally been employed, however chemical methods for the synthesis of NPs require the use of numerous highly toxic reagents, resulting in the production of environmentally harmful residues. Recently biological synthesis of nanoparticles has emerged as a promising and eco-friendly alternative, where extremophilic microorganisms and their enzymes play a key role. In this work the primary objective is to demonstrate the capability of two extremophilic microorganisms, isolated both from low temperature extreme environments, Pseudomonas aeruginosa and Geobacillus sp. ID17 for the biosynthesis of ferromagnetic NPs, specifically iron oxide NPs generated both intra and extracellularly.